Knowledge and innovation for agricultural development - Asenso-Okyere, Kwadwo; Davis, Kristin E. (International Food Policy Research Institute, 2009)
Every day, millions of rural people who depend on agriculture confront technical, economic, social, cultural, and traditional obstacles to improving their livelihoods. To cope with these obstacles, the rural poor draw on indigenous knowledge and innovate through local experimentation and adaptation. Indigenous knowledge alone, however, is not enough to deal with the complex problems facing the agricultural sector. Emerging issues such as high food prices, climate change, and demands for biofuels require complementary knowledge from formal agricultural research and development (R&D) and support from policies and other institutions. Formal and informal knowledge and innovation must therefore be linked to accelerate sustainable agricultural development. Knowledge, defined as organized or processed information or data, is fundamental in the pursuit of innovation. For innovation to occur, knowledge must be created, accumulated, shared, and used. Innovations—new ideas, practices, or products that are successfully introduced into economic or social processes— can involve technologies, organizations, institutions, or policies. Innovation means putting ideas, knowledge, and technology to work in a manner that brings about a significant improvement in performance or product quality.